A three‐dimensional free‐breathing sequence for simultaneous myocardial T1 and T2 mapping. Issue 2 (4th November 2018) - Guo, Rui; Chen, Zhensen; Herzka, Daniel A.; Luo, Jianwen; Ding, Haiyan
Abstract : Purpose: The aim of this study was to develop, test and validate a 3D free‐breathing technique for simultaneous measurement of native myocardial T1 and T2 . Methods: The proposed 3D technique acquires five fat‐suppressed electrocardiogram‐triggered respiratory navigator‐gated spoiled gradient echo volumes in an interleaved manner. Four volumes are prepared using a combination of nonselective saturation and T2 preparation. One volume is acquired with fully recovered longitudinal magnetization for accuracy during parametric fitting. Performance of the technique was validated through numerical simulations, phantom experiments and in vivo experiments in 15 healthy human subjects. Results: Simulations and phantom experiments show that the measured T1 and T2 are largely insensitive to heart rate. In vivo whole‐heart maps with a voxel size of 1.5 × 1.5 × 16 mm 3 were acquired without parallel imaging within 8 min including respiratory gating efficiency. The in vivo parametric maps were homogeneous (coefficients of variation of left ventricle myocardium were 6.0% ± 0.8% and 10.2% ± 3.4% for T1 and T2 maps, respectively), with an average T1 value of 1470 ± 59.2 ms and T2 value of 41.6 ± 1.8 ms Conclusions: The proposed 3D technique allows for measurement of whole‐heart T1 and T2 with preserved accuracy and precision in a single scan.